A micro-nanomechanical testing method for anisotropic properties of two-dimensional functional materials

Use PDMS to assist peeling and angle to distinguish the Raman spectrum recognition of the main axis direction, combined with MEMS in situ stretch technology, solve the problem of various heterosexual performance measurement of two -dimensional materials, and realize the high -precision Yang's modulus, broken strength and response limit limit The measurement of the two -dimensional material application has been widened.

CN115046817BActive Publication Date: 2025-01-24BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210465768.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-01-24
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine the anisotropic mechanical properties of two-dimensional materials, mainly due to challenges in preparation and processing, precise sample positioning and transfer, effective controllable loading of large-scale strains, and accurate determination of basic mechanical parameters.

Method used

The test sample was prepared using a polydimethylsiloxane (PDMS)-assisted exfoliation method, the main axis direction was identified through angle-resolved Raman spectroscopy, the rectangular strip sample was processed using focused ion beam or reactive ion etching, and the sample was processed in situ through MEMS The tensile device performs in-situ tensile tests and records load-displacement curves to calculate Young's modulus, breaking strength, and tensile ultimate strain of anisotropic materials.

Benefits of technology

It achieves high-precision testing of the anisotropic mechanical properties of two-dimensional functional materials. It can accurately measure the Young's modulus, fracture strength and strain limit of the material, with high resolution and repeatability, and can fully understand the in-plane surface of the material. Differences in mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115046817B_ABST
    Figure CN115046817B_ABST
Patent Text Reader

Abstract

The present application provides a micro-nanomechanical testing method for the anisotropy of a two-dimensional functional material, the technical key points of which are: firstly, a large-area uniform anisotropic material is prepared by a polydimethylsiloxane-assisted peeling method; then, the main axis direction is identified by angle-resolved Raman spectroscopy; then, the sample is processed into a rectangular strip specimen along different crystal axis directions by a focused ion beam method or a reactive ion etching method, and the specimen is transferred to a MEMS in-situ stretching chip by a probe transfer method, and the two main axis directions of the anisotropic material are respectively stretched in situ in combination with scanning electron microscopy technology; in the above-mentioned in-situ stretching test, the tensile deformation and fracture process of the material are visualized in situ while recording the load-strain curve; at the same time, a uniaxial stress model is established to calculate the stress-strain curve of the specimen, so as to achieve a comprehensive understanding of the differences in the in-plane mechanical properties of the anisotropic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of two-dimensional nanomaterials, and in particular to a micro-nanomechanical testing method for anisotropic two-dimensional functional materials. Background Art

[0002] The successful exfoliation of graphene in 2004 set off a craze for two-dimensional materials. Compared with bulk materials, two-dimensional materials with unique structures have covalently bonded atoms in the plane and low defect density, which makes two-dimensional materials have strong in-plane mechanical properties and can withstand large elastic strains without breaking. For example, the Young's modulus of a single layer of graphene is about 1TPa and the fracture strength is 130GPa. Its strength is expected to exceed any known bulk material. Therefore, the field of engineering applications of two-dimensional materials has great development potential.

[0003] In recent years, low-symmetry materials such as black arsenic and black phosphorus have attracted widespread attention from researchers. The excellent in-plane anisotropy gives two-dimensional materials a new degree of freedom. However, the anisotropic mechanical properties of two-dimensional materials are difficult to accurately measure and face many challenges, mainly in the preparation and processing of two-dimensional materials, precise positioning and transfer of samples, effective controllable loading of a large range of strains, and accurate measurement of basic mechanical parameters. Therefore, it is crucial to develop anisotropic mechanical property testing methods for two-dimensional functional materials.

[0004] At present, there are two main types of methods for measuring the in-plane mechanical properties of two-dimensional materials (see reference: Wang Guorui, Liu Luqi, Zhang Zhong. A review of experimental mechanics of two-dimensional materials [J]. Experimental Mechanics, 2017, 32(5):13):

[0005] The first type is direct methods, such as atomic force microscopy measurement, nanoindentation measurement, etc. Although direct methods can directly obtain load-displacement curves, complex models need to be established to solve parameters such as Young's modulus. In addition, the mechanical signal obtained during the experiment is a local response of the contact area between the material and the needle tip, forming a highly uneven stress-strain field, making it difficult to obtain the overall inherent mechanical properties of the material from experimental measurements. In addition, the load provided by the direct method is small, and it cannot realize the fracture performance test of thick layer materials, which has certain limitations.

[0006] The second type is an indirect measurement method based on Raman spectroscopy, which measures the material strain through the Raman spectral frequency shift and compares the strain with the numerical simulation based on the finite element method to estimate the Young's modulus of the material. Since the Raman frequency shift is affected by many factors such as sample thickness and thermal effects, the test error of this method is large. In addition, the test results are relatively simple and cannot realize the study of fracture behavior. Summary of the invention

[0007] The purpose of this application is to provide a micro-nanomechanical testing method for the anisotropy of two-dimensional functional materials in response to the above-mentioned deficiencies in the prior art.

[0008] The technical solution of this application is as follows:

[0009] A micro-nanomechanical testing method for anisotropy of two-dimensional functional materials comprises the following steps:

[0010] S100, preparing test samples, including S101 and S102;

[0011] S101, peeling the two-dimensional material to the PDMS surface, and transferring it to the SiO2 / Si surface by a dry transfer method to form a test sample;

[0012] S102, measuring sample thickness;

[0013] S200, crystal orientation identification, determining the principal axis direction of the sample;

[0014] S300, preparing two rectangular strip specimens: processing the sample into rectangular strip specimens along different principal axis directions (i.e., the length direction of one rectangular strip is one principal axis direction; the length direction of the other rectangular strip is another principal axis direction);

[0015] S400, preparation of a stretching device: making each rectangular strip into a separate stretching device; including S401 and S402;

[0016] S401, transferring the rectangular strip sample in S300 from the SiO2 / Si surface to the channel position of the MEMS in-situ stretching device;

[0017] S402, using a focused ion beam deposition method to deposit Pt at both ends of the sample for fixation to prevent the sample from slipping during the stretching process, thereby completing the preparation of the stretching device;

[0018] S500, in-situ tensile test: two tensile devices in different directions are installed in the nanomechanical testing system respectively, and then the whole device is installed in the SEM scanning electron microscope chamber to observe the entire tensile test process in situ;

[0019] The relative displacement between the micro-force sensing probe and the two hooks of the stretching chip is used to apply the load to the suspended sample through the cantilever beam movable part of the MEMS. The micro-force sensing probe is responsible for recording the load and displacement changes, thereby obtaining the corresponding load-displacement curve.

[0020] S600, data processing: including steps S601 and S602;

[0021] S601, based on the data obtained in S500, determine the two-dimensional Young's modulus E of the two-dimensional functional material in two directions of anisotropy 2D , three-dimensional Young's modulus E 3D ;

[0022] S602, determine the Young's modulus E and fracture strength σ of the two-dimensional functional material in two directions of anisotropy max , tensile limit strain ε max .

[0023] Furthermore, S101 also includes: using tape to peel off the two-dimensional material to the PDMS surface through a PDMS-assisted peeling method, selecting a large area sample with uniform thickness under a microscope, and transferring it to the SiO2 / Si substrate surface through a dry transfer method.

[0024] Further, in S102: the method of measuring the thickness of the sample is: accurately measuring the thickness of the sample by an atomic force microscope.

[0025] Further, in S200: the main axis direction of the sample is determined by building an angle-resolved Raman optical path to test the angle-resolved polarization Raman spectrum of the sample and determine the two main axis directions of the sample.

[0026] Further, S300 also includes: according to the two main axis directions of the crystal determined in S200, cutting the sample into rectangular strip samples along the two main axis directions by using a reactive ion etching method;

[0027] The sample size was set to 10 μm × 1 μm;

[0028] The reactive ion etching atmosphere is selected as CHF3:O2=45:5sccm, the ignition power is selected as 40W, and the pressure is 150mtorr.

[0029] Furthermore, S401 also includes: using a probe with a diameter of 1 μm to transfer the samples in two directions to two MEMS tensile devices respectively, and using the probe to adjust the position of the sample at any time so that it remains perpendicular to the channel;

[0030] S402 also includes: the thickness of the deposited Pt needs to be greater than the thickness of the sample.

[0031] Furthermore, S500 also includes: the voltage of the SEM is maintained at 2 kV.

[0032] Furthermore, the fixed tensile displacement rate in S500 is 0.0025 μm / s.

[0033] Furthermore, S601, the two-dimensional Young's modulus E 2D and the three-dimensional Young's modulus E 3D Calculated using the following formula:

[0034]

[0035]

[0036] k represents the tensile stiffness of the specimen, T represents the thickness of the material, W represents the width of the material, and L represents the length of the material.

[0037] Further, S602, the stress-strain curves of the samples of the anisotropic material in two directions can be obtained by the in-situ stretching method, and then the Young's modulus E and the fracture strength σ of the anisotropic material in two directions can be obtained. max , tensile limit strain ε max ;

[0038] The stress σ and strain ε are calculated using the following formula:

[0039]

[0040] Where F represents the known external load; A represents the cross-sectional area of ​​the specimen; T represents the thickness of the material; W represents the width of the material; L represents the length of the material, and ΔL represents the elongation of the specimen;

[0041] a. In the elastic phase region of the stress-strain curve, Young's modulus E can be measured:

[0042]

[0043] b. After the elastic stage in the stress-strain curve, if the load drops suddenly, the material will undergo brittle fracture behavior, and its fracture strength σ max and the tensile limit strain ε max It can be obtained by the following formula:

[0044]

[0045] Among them, F max Indicates the maximum breaking force of the specimen, ΔL max Indicates the maximum elongation of the specimen.

[0046] The beneficial effects of this application are:

[0047] First, in response to the problems faced by the current testing technology for the modulus of two-dimensional anisotropic materials, this application proposes the following testing method:

[0048] Firstly, a large-area uniform anisotropic material is prepared by using a polydimethylsiloxane dimethyl silicone polymer (PDMS)-assisted peeling method;

[0049] Then, the principal axis direction was identified by angle-resolved Raman spectroscopy;

[0050] Then, the sample is processed into rectangular strip specimens along different crystal axis directions by focused ion beam method or reactive ion etching method, and the sample is transferred to the MEMS in-situ stretching chip by probe transfer method, and the two main axis directions of the anisotropic material are stretched in-situ by combining the scanning electron microscope (SEM) technology;

[0051] In the above-mentioned in-situ tensile test, the load-strain curve is recorded while the tensile deformation and fracture process of the material are visualized in situ; at the same time, a uniaxial stress model is established to calculate the stress-strain curve of the specimen, thereby achieving a comprehensive understanding of the differences in the in-plane mechanical properties of anisotropic materials.

[0052] Second, this application provides a direct, effective, universal, high-precision mechanical testing technology that can achieve large-scale controllable uniform loading. It can accurately measure the basic mechanical parameters of the material, such as Young's modulus, fracture strength, and strain limit. At the same time, it combines high-resolution electron microscopy technology to visualize the stretching process in situ and accurately quantify the mechanical behavior of the material at the micro-nano scale.

[0053] Third, compared with the existing low-dimensional material mechanical property measurement method, the present invention has the following advantages:

[0054] 3.1 The strain non-local response generated by this method can achieve controllable uniform strain loading over a large range in the plane.

[0055] 3.2 This method does not rely on any strain transfer medium, and the load is directly and effectively applied to the material, without the problem of low strain transfer efficiency.

[0056] 3.3 This method can achieve a wide range of loads and displacements from 0.5nN-200mN and 0.05nm-21mm, with an accuracy of 500pN and 50pm respectively, with sufficiently high resolution and repeatability.

[0057] 3.4 This method can not only measure the two-dimensional and three-dimensional Young's modulus of low-dimensional materials in different directions, but also identify the fracture type of the material according to the stress-strain curve, and further obtain the basic mechanical parameters such as the maximum fracture force, fracture strength and tensile limit strain of the material. It can provide a more comprehensive understanding of the in-plane mechanical properties of the material and broaden the application field of anisotropic materials.

[0058] 3.5 This method has the advantage of in-situ visualization of SEM high-resolution electron microscopy technology, which can timely track the fracture process of the material, observe the fracture morphology of the material, and help to understand the fracture mechanism of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The present application is further described in detail below in conjunction with the embodiments in the accompanying drawings, but does not constitute any limitation to the present application.

[0060] Figure 1 : Optical microscope image of black arsenic sample.

[0061] Figure 2 : Schematic diagram of MEMS in-situ stretching.

[0062] Figure 3 : Load-displacement curves of black arsenic sample in armchair direction.

[0063] Figure 4 : Load-displacement curves of black arsenic sample in zigzag direction.

[0064] Figure 5 : Stress-strain curves of black arsenic samples in two directions. DETAILED DESCRIPTION

[0065] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The embodiments only provide one way to implement the proposed innovation, but are not the only one. It does not exclude the use of other ways to implement the above-mentioned inventions.

[0066] Example 1: A high-precision test method for anisotropic micro-nanomechanics of low-dimensional functional materials

[0067] Combined with Figure 1 To Attachment Figure 2 As shown, a test method for the anisotropic micro-nanomechanical properties of low-dimensional materials uses a micro-electromechanical systems (MEMS) stretching device to perform high-precision testing of the anisotropic micro-nanomechanics of low-dimensional functional materials. Taking black arsenic material as an example, it includes the following steps:

[0068] Step (1): Prepare samples.

[0069] a. Using 3M tape, the two-dimensional material was peeled off to the PDMS surface by PDMS (polydimethylsiloxane) assisted peeling method, and a large area of ​​black arsenic sample with uniform thickness was selected under a microscope, and then transferred to the grooved substrate surface of SiO2 / Si by dry transfer;

[0070] b. Accurately measure the sample thickness by atomic force microscopy: Use the Tipping mode in the atomic force microscope (Atomic Force Microscopy) to accurately characterize the sample morphology, measure the sample thickness, and observe whether the sample surface thickness is uniform. The final sample thickness value is 106.7nm.

[0071] Step (2): Crystal orientation identification.

[0072] This application realizes the test of angle-resolved polarization Raman spectrum of black arsenic samples under parallel configuration optical paths by building an angle-resolved Raman optical path. The direction of laser polarization is known, and the Raman intensity of the typical vibration peak of the sample reaches a local extreme value when the laser polarization direction is parallel to the main axis direction of the crystal to determine the main axis direction of the crystal (according to the angle-resolved Raman test method in the patent with application number 202210187472.7, the main axis direction of the black arsenic crystal can be identified). In addition, when the sample thickness is greater than 100nm, anisotropic absorption and interference effects will not affect the extreme direction of the Ag mode, that is, the maximum value of the Ag mode Raman intensity is the Armchair direction.

[0073] Step (3): Preparation of rectangular strip specimens.

[0074] Use micro-nano processing methods such as focused ion beam or reactive ion etching to process the sample into rectangular strip samples along different main axis directions: According to step 2, the two main axis directions of the crystal are known, and the black arsenic sample is cut into rectangular strip samples along the two main axis directions by using micro-nano processing technology electron beam exposure combined with reactive ion etching method, and the sample size is set to 10μm×1μm. Among them, CHF3:O2=45:5sccm is selected for reactive ion etching atmosphere, 40W is selected for ignition power, and the pressure is 150mtorr. It is known that the etching rate of the black arsenic sample is 2.5nm / s, so the etching time is 60s, and the sample preparation can be completed, such as Figure 1 shown.

[0075] Step (4): Preparation of the stretched device.

[0076] By using the probe transfer method, a 1μm probe was used to transfer the rectangular strip sample from the silicon substrate surface to the channel position of the MEMS in-situ stretching device, and the probe was used to adjust the sample position to ensure that the rectangular strip and the channel remained perpendicular. Further, Pt was deposited at both ends of the sample using the focused ion beam deposition method to fix it, preventing the sample from slipping during the stretching process, and completing the preparation of the stretching device.

[0077] Specifically, for anisotropic materials, the measurement of the in-plane anisotropic Young's modulus requires the precise transfer of samples in different directions to the micro-test area. Therefore, the present invention uses a probe with a diameter of 1 μm to transfer black arsenic samples in two directions to two MEMS stretching devices, and uses the probe to adjust the position of the black arsenic sample at any time to keep it perpendicular to the channel. In addition, in order to ensure that the sample does not slip during the stretching process, it is necessary to use a focused ion beam deposition method to deposit metal Pt at both ends of the sample to fix the sample. The thickness of the deposited Pt must be greater than the sample thickness, such as Figure 2 As shown in the enlarged figure.

[0078] Step (5): In-situ tensile test.

[0079] The MEMS tensile devices in two different directions were installed in the nanomechanical testing system, and then installed as a whole in the SEM scanning electron microscope chamber. The entire tensile test process was observed in situ and the two-dimensional and three-dimensional Young's modulus of the sample were calculated:

[0080] In order to reduce the influence of the electron beam effect, the SEM should be operated at a low voltage. Therefore, the voltage of this experiment is kept at 2kV throughout the whole process, which can ensure imaging while reducing the damage to the sample caused by the electron beam. At the beginning of the stretching experiment, a fixed stretching displacement rate of 0.0025μm / s was selected. The relative displacement between the micro-force sensing probe and the two hooks of the stretching chip is used to apply the load to the suspended sample through the cantilever beam movable part of the MEMS. The schematic diagram is shown in the figure. Figure 2 shown.

[0081] Step (6): Mechanical model and data processing.

[0082] a. Record the load and displacement changes through the micro-force sensor probe to obtain the corresponding load-displacement curve.

[0083] According to the load-displacement curve, the tensile stiffness k of the sample can be obtained (force / displacement is k, and the k obtained by the two tensile devices is different), and the two-dimensional Young's modulus E can be calculated. 2D and the three-dimensional Young's modulus E 3D (k is different, so the E of the two-dimensional functional material in two directions can be obtained 2D 、E 3D ):

[0084]

[0085]

[0086] k represents the tensile stiffness of the specimen, T represents the thickness of the material, W represents the width of the material, and L represents the length of the material.

[0087] b. Establishment of uniaxial stress model.

[0088] Since Pt needs to be deposited at both ends of the strip black arsenic sample for fixation, the stress / strain state of the sample is not completely uniform. The lateral stress of the central suspended part is zero, while the two ends of the sample are constrained and the lateral strain of the clamped part is limited. For samples with a large aspect ratio, it is more reasonable to use a uniaxial stress model than a uniaxial strain model in most areas of the sample.

[0089] According to the continuity assumption and plane assumption, we can get:

[0090]

[0091] Among them, σ represents the stress on the specimen; F represents the known external load; A represents the cross-sectional area of ​​the specimen; T represents the thickness of the material; W represents the width of the material; L represents the length of the material, ΔL represents the elongation of the specimen (W, L, ΔL can be measured by SEM); ε represents the strain borne by the specimen.

[0092] Therefore, the stress-strain curves of the samples in two directions of the anisotropic material can be obtained by the in-situ stretching method.

[0093] For the stress-strain curve, three parameters can be obtained: Young's modulus, maximum breaking force, and maximum elongation.

[0094] In the elastic phase of the stress-strain curve, the stress-strain of the material is proportional to each other. According to Hooke's law formula:

[0095]

[0096] Where E is a constant of proportionality related to the material, known as Young's modulus.

[0097] After the elastic stage, if the load drops suddenly, the material will undergo brittle fracture behavior, and its fracture strength σ max and the tensile limit strain ε max It can be obtained by the following formula:

[0098]

[0099] where F max Indicates the maximum breaking force of the sample. ΔL max Indicates the maximum elongation of the specimen.

[0100] In the experiment, Young's modulus, fracture strength and strain limit in two directions can be obtained, and the fracture behavior of the material can be seen intuitively; at the same time, with the help of SEM high-resolution electron microscopy technology, the entire stretching process can be visualized, and the differences in the fracture morphology of the material can be observed in time.

[0101] b.1 Tensile test in the armchair direction: In order to study the elastic properties of the material, the tests were performed at 60, 90, and 120 μN respectively. Figure 3 It can be seen that in the initial stage, the slope of the load-displacement curve is low, and the sample is in an unstretched state. At this time, the slope of the curve represents the stiffness of the MEMS tensile device itself. Then, as the displacement gradually increases, the black arsenic sample and the tensile device are both subjected to the load and enter the linear region. The slope of the curve is the sum of the stiffness of the black arsenic and the tensile device, and the value is 704.9N / m. In the process of loading and unloading cyclic tensile strain, each curve shows obvious linear behavior, indicating that the black arsenic surface has good elastic properties in the Armchair direction. At the same time, it proves that the MEMS device has excellent dynamic repeatability and reliability.

[0102] When the load reaches 119.6μN, the sample load drops suddenly and the sample fractures brittlely. Figure 3 As shown in the SEM inset, the fracture surface of the Armchair direction sample is perpendicular to the Zigzag lattice direction. After that, the load only acts on the MEMS tensile device, so the tensile stiffness of the device is 24.7N / m. Therefore, the tensile stiffness of the Armchair direction sample is 680.2N / m.

[0103] b.2 Tensile test in Zigzag direction: According to the same method, the tests were performed at 30, 60, and 90 μN in sequence. During the loading and unloading cyclic tensile strain, each curve showed obvious linear behavior, and the three curves almost completely overlapped, indicating that the Zigzag direction in the black arsenic surface was consistent with the Armchair direction, and also had good linear elastic properties. When the load reached 84.9 μN, the sample also showed brittle fracture behavior. According to the figure, the total tensile stiffness is 697.5 N / m, the device tensile stiffness is 44.3 N / m, and therefore the tensile stiffness of the sample in the Zigzag direction is 653.2 N / m.

[0104] b.3 Stress-strain curves of black arsenic materials in different directions: It is known that the thickness of the black arsenic sample in the Armchair direction is 106.7nm, and the length and width are 5.1μm and 1.5μm respectively; the length and width of the black arsenic sample in the Zigzag direction are 5.3μm and 1.2μm respectively, and the elongation of the two can be known from the SEM video image. According to the stress and strain calculation formula, the stress-strain curves in the two directions can be obtained, such as Figure 5 as shown in .

[0105] b.4 Young's modulus, fracture strength and strain limit of black arsenic samples in different directions: From the stress-strain curve, it can be seen that the mechanical properties in the two directions show significant anisotropy. Among them, the Young's modulus in the Zigzag direction is 35.4GPa, which is about 1.23 times that of the Armchair direction (28.6GPa). Therefore, the Armchair direction can withstand a larger strain limit of about 2.82%, and the Zigzag direction can only withstand a strain limit of 1.87%. The fracture strength in the Armchair direction (0.78GPa) is about 1.2 times that of the Zigzag direction (0.65GPa). In summary, the present invention can be used to fully understand the differences in mechanical properties in different directions within the surface of anisotropic materials, laying a good foundation for the application of anisotropic materials.

[0106] It should be noted that the test objects of the present invention include low-dimensional materials or micro-nano materials, but are not limited to two-dimensional anisotropic systems such as black arsenic.

[0107] It should be noted that: the present invention adopts PDMS polymer assisted peeling, but is not limited to other assisted peeling methods.

[0108] It should be noted that the material crystal orientation identification method used in the present invention is angle-resolved Raman spectroscopy, but is not limited to other crystal orientation identification methods.

[0109] It should be noted that the material processing method adopted in the present invention is reactive ion etching, but is not limited to other sample processing methods.

[0110] It should be noted that the present invention adopts a probe transfer method, but is not limited to other transfer methods.

[0111] It should be noted that: the present invention uses Pt to fix the two ends of the sample, but is not limited to other methods for fixing the sample.

[0112] It should be noted that the present invention uses MEMS devices from FemtoTools, but is not limited to other types of in-situ stretching devices with the same functions.

[0113] It should be noted that the present invention adopts SEM in-situ observation, but is not limited to other electron microscopy methods, such as transmission electron microscopy (TEM) and the like.

[0114] The above embodiments are preferred implementation modes of the present invention and are only used to facilitate the explanation of the present invention. They are not intended to limit the present invention in any form. Any person with ordinary knowledge in the relevant technical field, if they do not depart from the scope of the technical features of the present invention, can make equivalent embodiments by partial changes or modifications made by the technical contents disclosed in the present invention, and they still fall within the scope of the technical features of the present invention without departing from the technical features of the present invention.

Claims

1. A micro-nanomechanical testing method for anisotropy of two-dimensional functional materials, characterized in that: The steps include: S100, preparing a test sample: including steps S101 and S102; S101, transferring the two-dimensional material to the SiO2 / Si surface by using an assisted exfoliation method and a dry transfer method to form a test sample; S102, measuring sample thickness; S200, crystal orientation identification, determining the principal axis direction of the sample; S300, preparing two rectangular strip specimens: processing the samples along different main axis directions into rectangular strip specimens; S400, preparation of a stretching device: making each rectangular strip into a separate stretching device; including steps S401 and S402; S401, transferring the rectangular strip sample in S300 from the SiO2 / Si surface to the channel position of the MEMS in-situ stretching device; S402, using a focused ion beam deposition method to deposit Pt at both ends of the sample for fixation to prevent the sample from slipping during the stretching process, thereby completing the preparation of the stretching device; S500, in-situ tensile test: two tensile devices in different directions are installed in the nanomechanical testing system respectively, and then the whole device is installed in the SEM scanning electron microscope chamber to observe the entire tensile test process in situ; S600, data processing: including steps S601 and S602; S601, based on the data obtained in S500, determine the two-dimensional Young's modulus E of the two-dimensional functional material in two directions of anisotropy 2D , three-dimensional Young's modulus E 3D ; Two-dimensional Young's modulus E 2D and the three-dimensional Young's modulus E 3D Calculated using the following formula: Where k represents the tensile stiffness of the specimen, T represents the thickness of the material, W represents the width of the material, and L represents the length of the material; S602, determine the Young's modulus E and fracture strength σ of the two-dimensional functional material in two directions of anisotropy max and the tensile limit strain ε max ; The stress-strain curves of the anisotropic material in two directions can be obtained by the in-situ stretching method, and then the Young's modulus E and the fracture strength σ of the anisotropic material in two directions can be obtained. max , tensile limit strain ε max ; The stress σ and strain ε are calculated using the following formula: Where F represents the known external load; A represents the cross-sectional area of ​​the specimen; T represents the thickness of the material; W represents the width of the material; L represents the length of the material, and ΔL represents the elongation of the specimen; a. In the elastic phase region of the stress-strain curve, Young's modulus E can be measured: b. After the elastic stage in the stress-strain curve, if the load drops suddenly, the material will undergo brittle fracture behavior, and its fracture strength σ max and the tensile limit strain ε max It can be obtained by the following formula: Among them, F max Indicates the maximum breaking force of the specimen, ΔL max Indicates the maximum elongation of the specimen; S101 also includes: peeling the two-dimensional material to the PDMS surface by using a tape through a PDMS-assisted peeling method, selecting a large area sample with uniform thickness under a microscope, and transferring it to the SiO2 / Si surface by a dry transfer method; The method of determining the main axis direction of the sample in S200 is: by building an angle-resolved Raman optical path, testing the angle-resolved polarized Raman spectrum of the sample, and determining the two main axis directions of the sample; S300 also includes: according to the two main axis directions of the crystal determined in S200, the sample is cut into rectangular strip samples along the two main axis directions by using a reactive ion etching method; the sample size is set to 10μm×1μm; wherein the reactive ion etching atmosphere is selected as CHF3:O2=45:5sccm, the ignition power is selected as 40W, and the pressure is 150mtorr.

2. The micro-nanomechanical testing method for anisotropy of two-dimensional functional materials according to claim 1, characterized in that: In S102: the method of measuring the thickness of the sample is: accurately measuring the thickness of the sample by an atomic force microscope.

3. The micro-nanomechanical testing method for anisotropy of two-dimensional functional materials according to claim 1, characterized in that: S401 also includes: using a probe with a diameter of 1 μm to transfer the samples in two directions to two MEMS tensile devices respectively, and using the probe to adjust the position of the sample at any time so that it remains perpendicular to the channel; S402 also includes: the thickness of the deposited Pt needs to be greater than the thickness of the sample.

4. The micro-nanomechanical testing method for anisotropy of two-dimensional functional materials according to claim 1, characterized in that: S500 also includes: the voltage of the SEM is maintained at 2 kV.

5. The micro-nanomechanical testing method for anisotropy of two-dimensional functional materials according to claim 1, characterized in that: The fixed tensile displacement rate in S500 was 0.0025 nm / s.

Citation Information

Patent Citations

  • Crystal orientation determination method of two-dimensional black arsenic-based anisotropic material

    CN114563389A

  • Method for predicting ball-milling related tensile strength of graphene / aluminum nano composite material

    CN112945729A

  • Device and method for testing strain of low-dimensional material in different directions

    CN113375581A